Structural dynamics of free molecules and condensed matter. (May 2020) - Aseyev, S A; Akhmanov, A S; Girichev, G V; Ischenko, A A; Kochikov, I V; Panchenko, V Ya; Ryabov, E A
Abstract: Advances in the development of pulsed lasers provided a further breakthrough in the study of the structural dynamics of nuclei and electrons. As a result of this progress, the use of powerful femtosecond laser pulses, both for exciting a sample and for generating ultrashort (down to femto- and even subfemtosecond) photoelectron bunches synchronized with optical pulses for sensing matter, made it possible to observe the coherent dynamics of nuclei and electrons in samples at the required spatiotemporal scales. The possibility of direct observations of reaction processes is a major breakthrough in chemical physics. The many-particle potential is so complex that the degree of the interaction nonadiabaticity cannot be determined with an accuracy sufficient for predicting reaction paths. How can this information and a new look at the reaction dynamics be used in the future? This question arises in connection with the development of a new conceptual foundation of natural sciences incorporating the convergence of experimental and theoretical tools in studies of systems of any complexity with atomic resolution. In this approach, an 'atomic–molecular' movie is obtained by using mutually complementary information extracted from simultaneous studies of ultrafast electron (or X-ray) diffraction, spectroscopy, and the quantum dynamic theory of matter.